2017
DOI: 10.1080/20442041.2017.1294350
|View full text |Cite
|
Sign up to set email alerts
|

Fish communities in the Anthropocene: detecting drivers of changes in the deep peri-alpine Lake Geneva

Abstract: bIFreMer, Fisheries resources laboratory/Fisheries for the english Channel and north sea Unit (rBe/HMMn/rHPeB), Port-en-Bessin-Huppain, France; c Irstea, Ur eaBX aquatic ecosystems and Global Changes, Cestas, France ABSTRACT Climate forcing, in combination with local anthropogenic pressures, has drastically modified the physical and chemical properties of lakes worldwide, affecting the abundance and diversity of fish populations. In the context of these combined changes, understanding the interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
0
15
0
1
Order By: Relevance
“…Before the 2000s, catches were made up of only few cohorts, mainly age 2+ or 3+, while fishes older than 4 years were rare in the lake. In contrast, recent studies have shown that fish caught by French fishers in recent years are older (Anneville et al, 2017). Such a change in the age structure of the catches indicates a high level of recruitment and that the stock is not entirely harvested anymore.…”
Section: Factors Controlling Fish Communitiesmentioning
confidence: 85%
See 4 more Smart Citations
“…Before the 2000s, catches were made up of only few cohorts, mainly age 2+ or 3+, while fishes older than 4 years were rare in the lake. In contrast, recent studies have shown that fish caught by French fishers in recent years are older (Anneville et al, 2017). Such a change in the age structure of the catches indicates a high level of recruitment and that the stock is not entirely harvested anymore.…”
Section: Factors Controlling Fish Communitiesmentioning
confidence: 85%
“…From 1979 to the mid-1990s, whitefish contribution remained low and catches were dominated by percids that made up 76% of the total catches (41% for perch and 35% for roach). Since the 1990s, whitefish contributions started to increase again (up to 66% in 2010-2012) accompanied by a decrease in roach contributions while perch remained high ranging from 32% to 70% (Anneville et al, 2017).…”
Section: Lake Genevamentioning
confidence: 99%
See 3 more Smart Citations